Numerical Study of Flexural Performance of Reactive Powder Concrete Slabs with 15% Silica Fume and 30% Quartz Sand on Variations of Thickness and Long - Short Span Ratio - Wibowo, Wibowo; Setiono, Setiono; Ramadhan, Muhammad Naufal (Sustainable Civil Building Management and Engineering Journal, 2024)
As the development of infrastructure progresses rapidly, concrete technology is also required to continuously improve. Numerous studies on concrete technology have been conducted to meet these demands, one of which is the innovation of Reactive Powder Concrete (RPC) with 15% silica fume and 30% quartz sand. One application of reactive powder concrete in structural element design is the concrete slab. A concrete slab is a thin structure with a horizontal plane and loads perpendicular to the plane of the structure. Concrete slabs are designed to withstand bending loads due to bending moments caused by heavy loads, which are a combination of dead loads and live loads. Therefore, it is necessary to conduct flexural performance tests on concrete slabs to determine their ability to withstand loads that cause bending moments on the slabs. The research aims to compare the experimental test results with numerical analysis of the flexural performance of reactive powder concrete slabs with varying thicknesses and span length - width ratios. The test specimens for varying thicknesses measure 70 cm x 30 cm with thickness variations of 4 cm, 5 cm, 6 cm, and 7 cm. Meanwhile, the test specimens for varying span length-to-width ratios have a thickness of 5 cm and a length of 70 cm with span length-to-width ratio variations of 2,5; 2,7; 2,9; and 3,1. The research method used is non-linear finite element analysis with ATENA Engineering Červenka Consulting software. This research includes verification of experimental test results with numerical analysis results in terms of both maximum load and maximum deflection. The verification results of numerical analysis using ATENA Engineering Červenka Consulting software with experimental testing on both thickness variations and span length - width ratio variations show a corresponding trend curve based on the load-deflection graph, with the difference in maximum load and maximum deflection values between experimental test results and numerical analysis results being below 10%.